Hollow n-n type tin oxide / zinc stannate micron cube gas-sensitive material assembled by nanosheets as well as preparation method and application of hollow n-n type tin oxide / zinc stannate micron cube gas-sensitive material

The hollow n-n type SnO2/Zn2SnO4 micron cubic gas-sensitive material was prepared in one step by simple hydrothermal method, which solved the problem of insufficient sensitivity of existing gas sensors when detecting volatile organic compounds, and achieved high response, low detection limit and strong stability gas sensitive sensing performance.

CN119490220APending Publication Date: 2025-02-21ANHUI POLYTECHNIC UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411583683.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

When existing gas sensors detect volatile organic compounds such as formaldehyde, they have insufficient sensitivity, long response time and limited operating temperature, making it difficult to meet the needs of high sensitivity and low detection limits.

Method used

A hollow n-n type SnO2/Zn2SnO4 micron cubic gas-sensitive material assembled from nanosheets was prepared in one step. This material has more diffusion/transmission channels, rich active sites and larger specific surface area. , improves gas-sensitive sensing performance.

Benefits of technology

It achieves a high response to different volatile toxic and harmful gases, especially formaldehyde gases with the highest response and strong stability, and has an extremely low minimum detection limit, which significantly improves the performance of gas-sensitive sensors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119490220A_ABST
    Figure CN119490220A_ABST
Patent Text Reader

Abstract

The invention discloses a hollow n-n type tin oxide / zinc stannate micron cube gas sensitive material assembled by nanosheets as well as a preparation method and application thereof, the preparation method comprises the following steps: (1) dissolving tin salt, sodium hydroxide and CTAB in deionized water, then adding zinc salt, stirring until the tin salt, the sodium hydroxide and the CTAB are completely dissolved, and stirring at 45-55 DEG C for 2.5-3.5 hours; (2) carrying out hydrothermal reaction on the solution obtained in the step (1) at 175-185 DEG C for 7.5-8.5 hours, and then washing and drying; the hollow n-n type SnO2 / Zn2SnO4 micron cube gas-sensitive material has the advantages of more diffusion / transmission channels, abundant active sites, larger specific surface area and the like, so that an excellent gas-sensitive sensing behavior is generated, and the hollow n-n type SnO2 / Zn2SnO4 micron cube gas-sensitive material can be applied to a gas-sensitive sensor.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of gas-sensitive materials, and in particular relates to a hollow NN-type tin oxide / zinc stannate micrometer cubic block gas-sensitive material assembled from nanosheets, and a preparation method and application thereof. Background Art

[0002] Volatile organic compounds (VOCs) generally exhibit characteristics such as toxicity, pungent odor, volatility and flammability. Long-term exposure to VOCs poses a serious threat to human health. Formaldehyde is a colorless, irritating and toxic liquid used as a solvent and raw material in various industries. In 2017, the World Health Organization (WHO) classified formaldehyde as a Class 1 carcinogen. Its low boiling point (19°C) makes it easy to evaporate into vapor even at room temperature. When exposed to a certain concentration, inhalation of formaldehyde vapor can cause respiratory diseases, cancer and leukemia. According to the Air Quality Guidelines (GB / T18883-2002), the indoor formaldehyde vapor concentration should not exceed 0.1mg / m 3 Therefore, there is an urgent need to develop a gas sensor with high sensitivity and low detection limit to detect formaldehyde vapor to protect human health and the environment.

[0003] Gas sensors made of metal oxide semiconductors (MOS) have attracted extensive attention due to their ease of synthesis, affordability, and portability. MOS can be divided into two categories: p-type and n-type. SnO2, an n-type semiconductor with a band gap of 4.5 eV, is considered a promising choice for gas sensors due to its excellent electrical properties, high electron mobility, and corrosion resistance. However, gas sensors made of a single MOS often fail to meet the requirements of sensitivity, response / recovery time, and operating temperature. Strategies to enhance the sensing performance of gas sensors usually include controlling the morphology of SnO2, creating heterojunctions, forming porous / hollow micro / nanostructures, and modifying noble metals. Currently, sensing materials with rich heterojunctions and porous / hollow micro / nanostructures are expected to show excellent sensing performance. First, an additional electron depletion layer is formed on the contact surface, which significantly increases the resistance of the gas sensor. This promotes the generation of more active sites and oxygen species by enhancing the adsorption of oxygen molecules on the surface of the material, which may improve the sensing performance of the sensor. In addition, heterojunctions of different MOS lead to the production of grains with smaller sizes.

[0004] Zinc stannate (Zn2SnO4) is an n-type semiconductor with a band gap of 3.6 eV. Due to its high conductivity, excellent catalytic effect, high electron mobility (10-30cm 2 V -1 s -1) and good thermal stability, it has attracted widespread attention. Over the years, various methods have been developed to synthesize Zn2SnO4 with different morphologies and micro / nanostructures, including hydrothermal method, hydrothermal method combined with calcination, chemical bath deposition, solid-state reaction, and co-precipitation. However, so far, there are few reports on the one-step synthesis of hollow nn-type SnO2 / Zn2SnO4 microcubes with rich nn heterojunctions and nanosheet assembly. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a hollow nn-type SnO2 / Zn2SnO4 micron cubic block gas-sensitive material assembled from nanosheets, and a preparation method and application thereof. The hollow nn-type SnO2 / Zn2SnO4 micron cubic block gas-sensitive material has the advantages of more diffusion / transmission channels, abundant active sites and a larger specific surface area, thereby producing excellent gas-sensitive sensing behavior and can be used in gas sensors.

[0006] The technical solution adopted by the present invention is as follows:

[0007] A method for preparing a hollow nn-type SnO2 / Zn2SnO4 micron cubic gas-sensitive material assembled from nanosheets, the preparation method comprising the following steps:

[0008] (1) Dissolve tin salt, sodium hydroxide and CTAB in deionized water, then add zinc salt, stir until completely dissolved, and stir at 45-55° C. for 2.5-3.5 hours;

[0009] (2) The solution obtained in step (1) is subjected to a hydrothermal reaction at 175-185° C. for 7.5-8.5 hours, and then washed and dried to obtain a hollow nn-type SnO2 / Zn2SnO4 micron cubic gas-sensitive material assembled from nanosheets.

[0010] The mass ratio of the tin salt, sodium hydroxide, CTAB and zinc salt is 1:0.8-1.2:0.4-0.8:0.20-0.30.

[0011] The concentration of the tin salt in deionized water is 0.01-0.02 g / mL.

[0012] The tin salt is one of tin chloride, tin nitrate and tin sulfate.

[0013] The zinc salt is one of zinc chloride, zinc nitrate and zinc sulfate.

[0014] In step (2), the washing is performed by washing with deionized water for several times.

[0015] In step (2), the drying is performed at 55-65° C. for 4-6 hours.

[0016] The present invention also provides a hollow nn-type SnO2 / Zn2SnO4 micron cubic gas-sensitive material prepared according to the preparation method of the present invention, which has the morphology of a hollow micron cubic block, and the micron cubic block is assembled from nanosheets.

[0017] The present invention also provides the application of the hollow nn-type SnO2 / Zn2SnO4 micrometer cubic gas-sensitive material in a gas sensor.

[0018] The present invention also provides the application of the hollow nn-type SnO2 / Zn2SnO4 micrometer cubic gas-sensitive material in detecting volatile organic compounds, especially in detecting formaldehyde, methanol, ethanol, isopropanol, acetone and toluene.

[0019] The present invention provides a method for preparing a hollow nn-type SnO2 / Zn2SnO4 micron cubic gas-sensitive material assembled from nanosheets. A simple hydrothermal method is used to prepare a hollow nn-type SnO2 / Zn2SnO4 micron cubic composite material assembled from nanosheets in one step. The preparation operation is simple, the cost is low, and the preparation efficiency is high. The specific reaction is as follows: At a reaction temperature of 50°C and under continuous stirring, SnCl2·2H2O, ZnCl2 and CTAB gradually form small particles of zinc hydroxystannate in a NaOH aqueous solution, as shown in reaction formula (1). Then, the reaction is carried out at 180°C for 8 hours, and a large number of small particles are self-assembled to form hollow SnO2 / Zn2SnO4 micron cubic blocks, as shown in reaction formula (2).

[0020] Zn 2+ + Sn 2+ + 4OH - +H2O → ZnSn(OH)6 (1)

[0021] 2ZnSn(OH)6 → Zn2SnO4 + SnO2 + 6H2O (2)

[0022] The hollow nn-type SnO2 / Zn2SnO4 micron cubic gas-sensitive material provided by the present invention has better gas sensitivity than SnO2 material, and the improvement of its gas-sensitive performance is attributed to the following reasons: First, according to the Scherer formula, the average crystal sizes of SnO2 and SnO2 / Zn2SnO4 are 28.8nm and 13.7nm respectively. Small size means that a large number of Sn atoms become surface atoms, which promotes more surface reactions between oxygen species and the detected gas. Second, in terms of structure, the unique hollow microcubes assembled from nanosheets with rough surfaces are more conducive to promoting the transfer rate of gas molecules on the surface and in the structure. Therefore, more gas molecules can be adsorbed on both sides of the hollow microcube shell. Third, the hollow nn-type SnO2 / Zn2SnO4 microcube has a large specific surface area and can provide more surface active sites. Fourth, the introduction of zinc atoms can increase the content of catalytic active sites and promote the occurrence of more sensing reactions. Fifth, in addition, as shown in the UV-visible absorption spectrum, the band gap (Eg) of SnO2 / Zn2SnO4 is 3.34eV, which is smaller than that of SnO2 (Eg = 3.53eV). The smaller the Eg, the more conducive it is to promote more electrons to jump from the valence band of the material to the conduction band, thereby increasing the number of surface electrons. Sixth, due to the Fermi energy difference between SnO2 grains (4.5eV) and Zn2SnO4 grains (3.6eV). This will lead to interfacial charge separation and form a rich nn heterojunction at the interface, forming an additional electron depletion layer and increasing the resistance of the sensor. Seventh, according to the X-ray photoelectron spectroscopy (XPS) results, the vacancy oxygen (O vac ) relative percentage (24.5%) is higher than that of porous SnO2 micron flower (18.6%). This will produce more sensing reactions and active sites. Based on the above advantages, the present invention has excellent gas sensing performance.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] (1) The present invention adopts a simple hydrothermal method to prepare a nanosheet-assembled hollow nn-type SnO2 / Zn2SnO4 micrometer cubic block composite material in one step, which has simple preparation operation, low cost and high production efficiency.

[0025] (2) The hollow nn-type SnO2 / Zn2SnO4 micrometer cubic gas-sensitive material assembled from nanosheets provided by the present invention has a high response to different volatile toxic and harmful gases, especially the highest response to formaldehyde gas and strong stability, and at the same time has an extremely low minimum detection limit.

[0026] (3) The solution provided by the present invention has positive guiding significance for the sensitization operation of SnO2-based gas-sensitive materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 : SEM image of the hollow nn-type SnO2 / Zn2SnO4 composite material assembled from nanosheets prepared in Example 1;

[0028] Figure 2 : XRD patterns of the porous micron flower structure SnO2 gas-sensitive material assembled from the nanosheets prepared in Comparative Example 1 and the hollow nn-type SnO2 / Zn2SnO4 composite material assembled from the nanosheets prepared in Example 1;

[0029] Figure 3 : This is a diagram of a side-heated resistance sensor;

[0030] Figure 4 : (a) low magnification and (b) high magnification TEM images of the hollow nn-type SnO2 / Zn2SnO4 composite material assembled from nanosheets prepared in Example 1;

[0031] Figure 5 : SEM image of the porous micron flower structure SnO2 gas-sensitive material assembled from nanosheets prepared in Comparative Example 1;

[0032] Figure 6 : (a) is the UV-visible absorption spectra of the hollow nn-type SnO2 / Zn2SnO4 composite material assembled from the nanosheets prepared in Example 1 and the porous micron-flower structure SnO2 gas-sensitive material assembled from the nanosheets prepared in Comparative Example 1; (b) is the Kubelka-Munk transform reflectance spectra of the two;

[0033] Figure 7 : (a) is the BET graph of the hollow nn-type SnO2 / Zn2SnO4 composite material assembled from the nanosheets prepared in Example 1; (b) is the BET graph of the porous micron flower structure SnO2 gas-sensitive material assembled from the nanosheets prepared in Comparative Example 1;

[0034] Figure 8 :(a) is the optimal working temperature curve of the sensor prepared by the gas-sensitive materials in Comparative Example 1 and Example 1; (b) is the concentration gradient curve of formaldehyde gas at the optimal working temperature (230°C / 260°C);

[0035] Fig. 9 : (a) is a response diagram of the sensor prepared by the gas-sensitive materials in Example 1 and Comparative Example 1 to twelve volatile organic compounds at the optimal working temperature; (b) is a selectivity coefficient diagram of the sensor in Example 1;

[0036] Fig.10: (a) is the response recovery curve of the sensor prepared by the gas-sensitive material in Example 1 and (b) Comparative Example 1 to 100 ppm formaldehyde gas;

[0037] Fig.11 : A 28-day cycle diagram of the concentration of 100 ppm formaldehyde gas for the sensor prepared from the gas-sensitive material in Example 1 at the optimal working temperature;

[0038] Fig.12 : The concentration gradient curve of formaldehyde gas when the sensor prepared by the gas-sensitive material in Example 1 works at different humidity and the corresponding resistance curve in formaldehyde gas. DETAILED DESCRIPTION

[0039] The present invention is described in detail below with reference to the embodiments.

[0040] Example 1

[0041] A method for preparing a hollow nn-type SnO2 / Zn2SnO4 micron cubic gas-sensitive material assembled from nanosheets, the steps are as follows:

[0042] (1) Weigh 0.50 g SnCl2·2H2O, 0.50 g NaOH and 0.30 g CTAB and dissolve them in 30 ml deionized water respectively. Stir well and then add 0.13 g ZnCl2. Stir until the solid matter is completely dissolved.

[0043] (2) Place the mixed liquid in a water bath at 50°C for 3 hours while stirring continuously;

[0044] (3) The solution obtained in step (2) was transferred to a 50 mL autoclave, maintained at 180° C. for 8 hours, and taken out after cooling to room temperature. The obtained product was washed with deionized water several times, and then dried at 60° C. for 5 hours to obtain a hollow nn-type SnO2 / Zn2SnO4 micron cubic block composite material assembled by nanosheets.

[0045] The SEM and TEM images of the hollow nn-type SnO2 / Zn2SnO4 micrometer cubic composite material assembled from nanosheets prepared in this embodiment are shown in Figures 1 and 2. Figure 1 , 3 As shown in the figure, it can be seen that its morphology is a hollow micron cube assembled from nanosheets.

[0046] Its XRD pattern is as follows Figure 2 As shown, it can be seen that the composition of the product is SnO2 / Zn2SnO4.

[0047] Comparative Example 1

[0048] A method for preparing a porous micron flower structure SnO2 gas-sensitive material assembled from nanosheets, the steps are as follows:

[0049] 1) Weigh 0.60 g SnCl2·2H2O, 0.50 g NaOH and 0.30 g CTAB and dissolve them in 30 ml deionized water respectively, and stir until the solid matter is completely dissolved;

[0050] (2) Place the mixed liquid in a water bath at 50°C for 3 hours while stirring continuously;

[0051] (3) The solution obtained in step (2) was transferred to a 50 mL autoclave, maintained at 180° C. for 8 hours, and taken out after cooling to room temperature. The obtained product was washed with deionized water several times, and then dried at 60° C. for 5 hours. The dried product was placed in a muffle furnace and calcined at 700° C. for 1 hour at a heating rate of 10° C. / min in an air atmosphere, thereby obtaining a porous micron flower structure SnO2 gas sensing material assembled by nanosheets, and its SEM image is shown as follows: Figure 5 As shown in the figure, it can be seen that its morphology is a porous micron flower assembled from nanosheets. Its XRD pattern is as follows Figure 5 As shown, it can be seen that the composition of the product is SnO2.

[0052] The UV-visible absorption spectra of the gas-sensitive materials prepared in Example 1 and Comparative Example 1 are shown in FIG. Figure 6 As shown in the figure, it can be seen that the band gap (Eg) of SnO2 / Zn2SnO4 is 3.34eV, which is smaller than the band gap of SnO2 (Eg = 3.53eV). The smaller the Eg, the more electrons are promoted to jump from the valence band of the material to the conduction band, thereby increasing the number of surface electrons.

[0053] The BET diagrams of the gas-sensitive materials prepared in Example 1 and the comparative example are shown in FIG. Figure 7 As shown in the figure, it can be seen that both materials are obviously porous materials. The average pore diameters of the materials prepared in Example 1 and Comparative Example 1 are about 8 nanometers and 2.5 nanometers, respectively. Their specific surface areas are 64.98 m 2 g -1 and 11.91m 2 g -1 The larger the pore size and specific surface area, the more beneficial it is to provide more active sites and adsorb more gas molecules, thus showing better gas sensing performance.

[0054] Application Examples

[0055] 3 mg of the hollow nn-type SnO2 / Zn2SnO4 micron cubic composite material prepared in Example 1 and the porous micron flower structure SnO2 gas-sensitive material assembled from nanosheets prepared in Comparative Example 1 were placed in a mortar respectively, and then 300 microliters of a mixture of deionized water and ethanol in a volume ratio of 1:2 were dripped into the mortar and fully ground with the prepared sample until a uniform slurry was formed. The slurry was evenly coated on the ceramic tube, and then dried at 100°C for 2 hours. A uniform gas-sensitive material film will form on the surface of the ceramic tube. The four pins of the ceramic tube were fixed to the sensor base with solder, and a nickel-chromium alloy heating wire was introduced into the ceramic tube and connected to both ends of the ceramic tube. The manufactured gas sensor was aged at 200°C for 3 days. This is a side-heated resistive sensor, such as Figure 3 As shown, a indirectly heated resistive sensor is used as a test carrier. The device has low cost, small size, simple process, and is easy to mass produce.

[0056] In the test, the voltage applied to the end of the nickel-chromium alloy heating wire was adjusted to simulate the different operating temperatures of the gas sensor, and the optimal response temperature of each sensor to formaldehyde gas was tested. The results are as follows: Figure 8 As shown in Figure a, it can be seen from the figure that the optimal response temperatures of the gas sensors prepared from the gas-sensitive materials in Example 1 and Comparative Example 1 are 230°C and 260°C respectively, and it can be seen that the optimal response temperature of the gas sensor prepared from the gas-sensitive material in Example 1 is relatively low. At the optimal response temperature, the concentration gradient curves of the real-time response of each sensor to formaldehyde gas are as follows: Figure 8 As shown in Figure b, it can be seen from the figure that with the increase of formaldehyde gas concentration, the sensitivity of the sensor also increases significantly. And there is an obvious concentration gradient, which shows that there is a good linear relationship between the formaldehyde gas concentration and the sensor sensitivity. In addition, under the condition of contact with the same formaldehyde gas concentration, the sensitivity of the sensor prepared by the gas-sensitive material in Example 1 is significantly higher than the sensitivity of the sensor prepared by the gas-sensitive material in Comparative Example 1.

[0057] The sensing performance test was based on a static gas test system. During the test, the laboratory environment temperature was 28 °C. The sensor response test was performed on an electrochemical workstation (CHI-660E, Instrument Co., Ltd.), and the software displayed the current through the gas-sensitive material film on the sensor in real time. In this test system, the response is defined as S = I g / I a , where I a Represents the output current of the gas sensor in the reducing atmosphere to be measured, I gIndicates the input current of the gas sensor in air atmosphere. On the other hand, the response recovery time is defined as the time required for the gas sensor device to generate 90% of this current, which is measured from when it is placed in air atmosphere to when the current reaches a steady state when it is placed in a reducing atmosphere, respectively.

[0058] The sensor's response to each gas at the optimal response temperature is as follows: Fig. 9 As shown in the figure, it can be seen that the gas sensitivity of the sensor prepared using the hollow nn-type SnO2 / Zn2SnO4 micron cubic block composite material in Example 1 is significantly better than that of the sensor prepared using the porous micron flower structure SnO2 gas-sensitive material assembled from nanosheets in Comparative Example 1, and the sensor prepared from the gas-sensitive material in Example 1 has the best responsiveness to formaldehyde.

[0059] The response recovery curves of the sensors prepared using the gas-sensitive materials in Example 1 and Comparative Example 1 to 100 ppm formaldehyde gas are shown in FIG. Fig.10 As shown in the figure, it can be seen that the response and recovery time of the sensor prepared by the gas-sensitive material in Example 1 are 21 seconds and 11 seconds respectively. The response and recovery time of the sensor prepared by the gas-sensitive material in Comparative Example 1 are 18 seconds and 20 seconds respectively. It shows that the sensor prepared by the gas-sensitive material in Example 1 has a strong recovery ability.

[0060] The 28-day cycle graph of the sensor prepared using the hollow nn-type SnO2 / Zn2SnO4 micron cubic composite material in Example 1 for 100 ppm formaldehyde gas concentration at the optimal working temperature is as follows: Fig.11 As shown, it can be seen from the figure that the sensor prepared by the gas-sensitive material in Example 1 has better stability and repeatability.

[0061] The concentration gradient curve of the sensor prepared by the hollow nn-type SnO2 / Zn2SnO4 micron cubic composite material in Example 1 at different humidity and the corresponding resistance curve in the formaldehyde gas are as follows: Fig.12 As shown in a, b, and c in the figure, it can be seen from the figure that as the humidity in the air increases, the resistance of the sensor prepared by the gas-sensitive material in Example 1 continues to decrease; at different humidity, the sensitivity and resistance curves of the sensor in 100ppm formaldehyde gas are as shown in Fig.12 As shown in Figure d, it can be seen that when the humidity in the air increases, the resistance and sensitivity of the sensor decrease. This is because the increase in relative humidity will produce more water molecules, which occupy more active sites on the surface of the material, resulting in a decrease in the gas-sensing performance of the prepared sensor.

[0062] The above reference embodiments provide a detailed description of a hollow NN-type tin oxide / zinc stannate micrometer cubic gas-sensitive material assembled from nanosheets, its preparation method and application, which is illustrative rather than restrictive. Several embodiments can be listed according to the limited scope. Therefore, changes and modifications without departing from the overall concept of the present invention should fall within the scope of protection of the present invention.

Claims

1. A method for preparing a hollow nn-type SnO2 / Zn2SnO4 micron cubic gas-sensitive material assembled from nanosheets, characterized in that: The preparation method comprises the following steps: (1) Dissolve tin salt, sodium hydroxide and CTAB in deionized water, then add zinc salt, stir until completely dissolved, and stir at 45-55° C. for 2.5-3.5 hours; (2) The solution obtained in step (1) is subjected to a hydrothermal reaction at 175-185° C. for 7.5-8.5 hours, and then washed and dried to obtain a hollow nn-type SnO2 / Zn2SnO4 micron cubic gas-sensitive material assembled from nanosheets.

2. The preparation method according to claim 1, characterized in that: The mass ratio of the tin salt, sodium hydroxide, CTAB and zinc salt is 1:0.8-1.2:0.4-0.8:0.20-0.

30.

3. The preparation method according to claim 1, characterized in that: The concentration of the tin salt in deionized water is 0.01-0.02 g / mL.

4. The preparation method according to any one of claims 1 to 3, characterized in that: The tin salt is one of tin chloride, tin nitrate and tin sulfate.

5. The preparation method according to any one of claims 1 to 3, characterized in that: The zinc salt is one of zinc chloride, zinc nitrate and zinc sulfate.

6. The preparation method according to any one of claims 1 to 3, characterized in that: In step (2), the washing is performed by washing with deionized water for several times.

7. The preparation method according to any one of claims 1 to 3, characterized in that: In step (2), the drying is performed at 55-65° C. for 4-6 hours.

8. A hollow nn-type SnO2 / Zn2SnO4 micron cubic gas-sensitive material prepared by the preparation method according to any one of claims 1 to 7.

9. Application of the hollow nn-type SnO2 / Zn2SnO4 micron cubic gas-sensitive material as claimed in claim 8 in a gas sensor.

10. Use of the hollow nn-type SnO2 / Zn2SnO4 micrometer cubic gas-sensitive material as claimed in claim 8 in detecting volatile organic compounds.